2021
DOI: 10.1016/j.clml.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Non-Hodgkin's Lymphoma in HCV Patients in the United States Between 2013 and 2020: A Population-Based Study

Abstract: An association between non-Hodgkin's lymphoma (NHL) and hepatitis C virus (HCV) was recognized two decades ago with no recent studies. We studied database (Explorys, IBM) which includes records of over 72 million patients. Between June 2013 and June 2020, HCV-positive and HCV-negative populations were compared. NHL's risk in HCV positive group was higher than previously reported, with an odds ratio of 2.6. Hepatitis C virus (HCV) is a significant healthcare problem affecting ˜1% of the United States population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As with previous studies, including two large population-based case-control and cohort studies conducted in the USA and Denmark, we observed elevated incidence of pancreatic cancer, kidney cancer, lung cancer, and oropharyngeal cancer among people living with HCV infection ( 9 , 25 30 ). Among extrahepatic cancers, NHL has been reported to have the strongest association with chronic HCV infection ( 28 , 31 , 32 ). Higher proportions of problematic alcohol consumption, injection drug use, and comorbid medical conditions among individuals living with chronic HCV could partly explain the greater incidence of alcohol and/or tobacco-related cancers, namely oral, larynx, esophagus, lung, kidney, and pancreatic cancers in our cohort ( Table 1 ) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with previous studies, including two large population-based case-control and cohort studies conducted in the USA and Denmark, we observed elevated incidence of pancreatic cancer, kidney cancer, lung cancer, and oropharyngeal cancer among people living with HCV infection ( 9 , 25 30 ). Among extrahepatic cancers, NHL has been reported to have the strongest association with chronic HCV infection ( 28 , 31 , 32 ). Higher proportions of problematic alcohol consumption, injection drug use, and comorbid medical conditions among individuals living with chronic HCV could partly explain the greater incidence of alcohol and/or tobacco-related cancers, namely oral, larynx, esophagus, lung, kidney, and pancreatic cancers in our cohort ( Table 1 ) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biological mechanisms underlying elevated risks of extrahepatic cancers among individuals living with HCV infection are not well-understood; for NHL, the process seems to involve direct and indirect oncogenic expressions of HCV proteins (e.g., E2) which causes lymphoproliferative disorders such as B-cell continuous replication ( 32 , 35 37 ). Chronic kidney disease and oral lichen planus are known HCV-related extrahepatic manifestations which may correspondingly increase the risks of renal and oral cancers among people with HCV infection ( 35 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from liver transplantation, chronic hepatitis C infection is also known to be associated with an increased risk of developing HM predominantly of B-cell type but not AML, whatever the level of liver fibrosis (4,11,12,19). The underlying pathogenesis is most likely the chronic and continuous antigen stimulation leading to a permanent B-cell response with subsequent genetic mutation and finally clonal and malignant B-cell proliferations (20).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the increased risk of HCV-associated lymphoma was persistent across genders, between Caucasians and African-Americans, and across age groups. While the risk of NHL in the HCV-negative population was higher in Caucasians than African-Americans (OR 1.8, 95% CI 1.7-1.8), the risk of HCV-associated NHL was not different [43]. The researchers also found that there were few cases of NHL in patients under 40 years of age.…”
Section: Epidemiology Of Hcv-infected B-cell Lymphomamentioning
confidence: 94%